The Effect of FOXC2-AS1 on White Adipocyte Browning and the Possible Regulatory Mechanism - Wang, Yan; Hua, Siyu; Cui, Xianwei; Cao, Yan; Wen, Juan; Chi, Xia; Ji, Chenbo; Pang, LingXia; You, Lianghui (Frontiers in Endocrinology, 2020)
Abstract: Obesity has become a worldwide epidemic, and obesity-related problems are becoming more severe in public health. Increasing brown adipose tissue (BAT) mass or/and activity in mice and humans has been demonstrated to help lose weight and improve whole-body metabolism. Studies on the conversion of white adipose tissue (WAT) to BAT under certain conditions have provided new possibilities for treating obesity and the related disorders. It has been established that long non-coding RNAs (lncRNAs) play an important role in the regulation of mouse adipocyte differentiation and thermogenic programs; however, the function and potential mechanism of lncRNA in the process of human white adipocyte browning remains unclear. In the present study, we identified a lncRNA called Forkhead Box C2 antisense RNA 1 (FOXC2-AS1), which was first identified in osteosarcoma, and it was highly expressed in human adipocytes but decreased during the white adipocyte differentiation program. FOXC2-AS1 expression was also induced by thermogenic agent forskolin. Lentivirus-mediated overexpression of FOXC2-AS1 in human white adipocytes did not affect lipid drop accumulation, but significantly promoted the browning phenotype, as revealed by the increased respiratory capacity and the enhanced protein expression levels of brown adipocyte-specific markers. In contrast, inhibiting FOXC2-AS1 with small interfering RNA led to attenuated thermogenic capacity in human white adipocytes. RNA-sequencing analysis and western blot were used to identify a possible regulatory role of the autophagy signaling pathway in FOXC2-AS1 to mediate white-to-brown adipocyte conversion. Autophagy inhibitor 3-methyladenine (3-MA) restored the reduction of UCP1 protein level and thermogenic capacity those were caused by the inhibition of FOXC2-AS1. Overall, the present study characterized the potential role of FOXC2-AS1 and further identified a lncRNA-mediated mechanism for inducing browning of human white adipocytes and maintaining thermogenesis, further providing a potential strategy for treating obesity and related disorder.